Lucky image performance simulation on the basis of optical turbulence data obtained on Mt. Shatdzhatmaz - Safonov, B.S. (Advances in Astronomy and Space Physics, 2011)
Lucky imaging is a method allowing to achieve difiraction resolution on a moderate ground-based telescopes with the cost of magnitude limitation. To adequately evaluate capabilities of this technique for a given place (Mt. Shatdzhatmaz) we performed a Monte Carlo numerical simulation taking into account properties of optical turbulence measured there. Statistics of lucky imaging isoplanatic angle was evaluated on the basis of these data. Optimal atmospheric conditions for lucky imaging were obtained.